+0  
 
0
303
1
avatar

solve for h

SA=2pir^2+2pirh

Guest Apr 22, 2017

Best Answer 

 #1
avatar+7153 
+3

SA = 2πr2  + 2πrh

 

Subtract 2πr2 from both sides of the equation.

SA - 2πr2 = 2πrh

 

Divide through by 2πr .

SA/(2πr) - r = h

hectictar  Apr 22, 2017
 #1
avatar+7153 
+3
Best Answer

SA = 2πr2  + 2πrh

 

Subtract 2πr2 from both sides of the equation.

SA - 2πr2 = 2πrh

 

Divide through by 2πr .

SA/(2πr) - r = h

hectictar  Apr 22, 2017

12 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.